Handling the heat: keeping water available for birds of the Tankwa Karoo Desert - Morar, Sean (Department of Biological Sciences, 2023)
Climate change poses one of the biggest risks to biodiversity globally. Africa is warming at twice the global average rate and African bird species are therefore at risk, particularly in desert environments where they are already operating near physiological limits. Desert air temperatures in the subtropical latitudes will rise by 3°-5°C by the end of the century. When air temperatures are higher than body temperature, birds must use evaporative cooling to avoid hyperthermia. However, evaporative cooling requires water and a tradeoff exists between hyperthermia and dehydration. For drinking species which need open water sources in order to rehydrate, this tradeoff is exacerbated by high operative temperatures on the ground near the water's edge during periods of extreme heat. This study assessed whether providing artificial shade at waterholes can buffer impacts of high temperature by increasing accessibility of water to birds, potentially facilitating persistence of desert bird communities under climate change. I used a before-after control-impact experimental design to test the impact of shade provision on visitation rates, species richness and the timing of visits by desert birds to waterholes in the Tankwa Karoo National Park of South Africa. Providing shade reduced afternoon waterside operative temperatures below lethal limits for many small passerine species and successfully buffered birds' visitation rates to the water's edge during hot periods, although species richness did not change. Overall bird visitation rates to waterholes increased in the afternoon relative to control sites in response to the addition of shade but decreased in the morning, likely due to a perceived/actual predation risk while operative temperatures were low and shade structures provided no thermal benefit. Responses to shade were species-specific, with the overall positive response driven in part by two common species: Grey-backed Sparrow-larks Eremopterix verticalis and Tractrac Chats Emarginata tractrac. Two species (Cape Sparrows Passer melanurus and White-throated Canaries Crithagra albogularis) responded negatively to the provision of shade. There was an observed shift in bird visitation rates from the morning to the afternoon at shaded structures, suggesting temperature as a primary driver in the use of shade. As temperatures increase under climate change, birds may be forced to drink more in the afternoon due to rising water demands for thermoregulation. Shade structures such as those trialed in this study may have the potential to facilitate this shift and keep water accessible to desert birds in the face of temperature increases.